Factors affecting the intention to adopt cloud accounting software in small and medium enterprises in Ho Chi Minh City - Nguyen, Thi Kieu Oanh; Phan, Thi Bich Ngoc; Ho, Van Cuong (Journal of Finance - Marketing Research, 2024)
In the trend of the digital economy along with the widespread Industrial Revolution 4.0, accounting work organization needs to innovate in applying information technology (IT) in the implementation and management of accounting tasks. Cloud accounting software is built based on the development achievements of Cloud Computing, data is stored on data center servers, helping to process data and accounting work anytime, anywhere. and on every device. This article aims to identify factors influencing the intention the adoption of cloud accounting software in small and medium enterprises (SMEs) in Ho Chi Minh City. Through data collection using questionnaires from 210 SMEs and using SPSS analysis tools, the research results show that there is an impact of factors such as perceived usefulness, perceived ease of use, manager support, social influences and application risks that affect the intention to apply cloud accounting software of these businesses. These results provide useful information to help business managers better understand the benefits of the application, the role and importance of IT application in general, and cloud accounting software in particular in business operations, contributing to improving accounting work at the business.